2014
DOI: 10.1007/s00894-014-2315-4
|View full text |Cite
|
Sign up to set email alerts
|

A detailed reactive cross section study of X + Li2 → Li + LiX, with X = H, D, T, and Mu

Abstract: In this work we apply quasiclassical trajectory theory to the X + Li2 → Li + LiX reactions, with X standing for H, D, T, and Mu, in order to determine dynamical properties such as state-to-state reactive cross-section, rotational, vibrational, and translational product distributions. By using the literature benchmark potential energy surface, we were able to predict the aforementioned dynamical property in remarkable qualitative agreement with data in the literature for the H + Li2 → Li + LiH channel. Particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…26 , which brought results laying way below the average, although the use of quasi-classical trajectories (QCT) might have seemed advisable given that the characteristics of the Li 2 H PES did not suggest a considerable tunneling contribution. Despite the endorsement by preliminary QCT calculations performed in ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 , which brought results laying way below the average, although the use of quasi-classical trajectories (QCT) might have seemed advisable given that the characteristics of the Li 2 H PES did not suggest a considerable tunneling contribution. Despite the endorsement by preliminary QCT calculations performed in ref.…”
Section: Resultsmentioning
confidence: 99%
“…This study concluded that the formation of LiH molecules which are ro-vibrationally excited by an amount of energy comparable to −Δ H in the particular H+Li 2 bimolecular exchange reaction is somewhat favored, a feature observed in similar reactions involving other alkali diatoms like K 2 , Rb 2 and Cs 2 3 . Besides, our research group also investigated the isotopic effects for the H+Li 2 reaction when hydrogen is substituted by muonium, deuterium or tritium, and we found that both quasi-classical 26 and quantum 27 results came to terms with the fact that the higher the isotope mass, the greater the cross section.…”
Section: Introductionmentioning
confidence: 99%